Uptake of agroforestry-based crop management in the semi-arid Sahel – Analysis of joint decisions and adoption determinants - Christian Grovermann; Christian Grovermann; Charles Rees; Charles Rees; Assane Beye; Tesfamicheal Wossen; Tahirou Abdoulaye; Harun Cicek; Harun Cicek (Frontiers in Sustainable Food Systems, 2023)
IntroductionAgroforestry plays a vital role in maintaining and developing the resilience and productivity of farms and landscapes. Scientific evidence from the Sahel region suggests that integration of trees and shrubs has the potential to improve temperature and moisture levels whilst providing bio-based fertilizer that contributes to increased yields of annual crops. However, little is known about the factors that influence the diffusion of agroforestry. This study examines joint decisions on the use of agroforestry alongside other complementary agricultural practices and disentangles agroforestry awareness from adoption and disadoption decisions.MethodsOur analysis is based on a comprehensive farm-level dataset covering almost 3,000 farm households in Mali and Senegal. A large number of adoption determinants are utilized, with a special focus on information access, information flows and social groups.ResultsThe findings suggest that extension access and training participation boost awareness of agroforestry-based soil fertility management, while information provided by public extension, NGOs and community members is strongly associated with higher adoption intensity. In the analysis of disadoption, farmer-to-farmers exchange in the community was found to be a key factor in the decision to maintain agroforestry use. Membership in cooperatives and youth groups appear to have a favorable effect on awareness and adoption in Mali, but less so in the Senegalese case. Similarly, only results from Mali show that adoption of agroforestry is accompanied by the adoption of other sustainable intensification practices and lower use of synthetic pesticides.DiscussionWe conclude that in order to support the transition to more widespread agroforestry-based soil fertility management, it is essential to strengthen public and NGO-based advisory systems that fully engage with local knowledge networks.